The status of body mass index on heart rate recovery in young adults: literature review - Nurvita Risdiana; Anjar Purniati; Dewi Puspita (Universitas Aisyiyah Yogyakarta, 2022)
The development of modern adaptation increases the prevalence of obesity with a characteristic of fat hoarding especially in young adults. Young adults are the most common users of gadgets, and they have sedentary lifestyle. Body Mass index (BMI) is the ratio of weight in kilogram (kg) and height that has been squared in meter (m) and becomes the easiest parameter to measure excess fat. Excessive fat accumulation can affect vagal reflex, causing an impact in Heart Rate Recovery (HRR). Delayed HRR or ≤ 12 bpm increases the risk of arrhythmia and sudden cardiac death. The purpose of this review is to determine the status of BMI on HRR in young adults. The searching for article reviews used electronic database with several databases namely PubMed, Ebscohost, Proquest, and Google scholar resulted nine eligible articles. Overweight decreased HRR and delaying vagal reactivation which increased the risk of death caused by sympathetic nerve dominance which increased the risk of heart attack. Based on the review result, the profile of anthropometry can describe the fitness status of the cardiovascular system.